2021
DOI: 10.1111/dom.14513
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sotagliflozin in patients with type 2 diabetes and severe renal impairment

Abstract: Aims: To assess the efficacy and safety of sotagliflozin, a dual inhibitor of sodiumglucose cotransporter-1 and -2, in adults with type 2 diabetes (T2D) and stage 4 chronic kidney disease (CKD4).Materials and Methods: This 52-week, phase 3, randomized (1:1:1), placebocontrolled trial evaluated sotagliflozin 200 mg and sotagliflozin 400 mg once daily in 277 patients with T2D and estimated glomerular filtration rate (eGFR) 15 to 30 mL/ min/1.73 m 2 . The primary endpoint was glycated haemoglobin (HbA1c) reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 34 publications
4
56
0
1
Order By: Relevance
“…The safety of sotagliflozin in patients with type 2 diabetes and renal impairment was also established in a recently published phase 3 trial, in which 277 patients with stage 4 chronic kidney disease were randomly assigned to sotaglifliozin or placebo. Overall, after 52 weeks, treatment with sotagliflozin resulted in sustained glycaemic control and an overall safe profile 17 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The safety of sotagliflozin in patients with type 2 diabetes and renal impairment was also established in a recently published phase 3 trial, in which 277 patients with stage 4 chronic kidney disease were randomly assigned to sotaglifliozin or placebo. Overall, after 52 weeks, treatment with sotagliflozin resulted in sustained glycaemic control and an overall safe profile 17 …”
Section: Discussionmentioning
confidence: 93%
“…The flow diagram of the study selection process is depicted in Figure S1. Eleven trials comprising 16 411 subjects were included in our systematic review and meta‐analysis 7,8,15‐23 . Study and participants’ baseline characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, 277 patients with stage 4 CKD were included in the study. The results demonstrated that the sotagliflozin group had fewer adverse cardiovascular events than in the placebo group [ 30 ]. Our study indicated that patients with stage 3a or 3b CKD had a much lower risk of adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%